2018
DOI: 10.3390/socsci8010004
|View full text |Cite
|
Sign up to set email alerts
|

A Socio-Structural Perspective on Family Model Preferences, Gender Roles and Work–Family Attitudes in Spain

Abstract: Since the early 1990s, the diversity of work–family arrangement models has increased in Spain. It is difficult to understand this phenomenon without attending to the Spanish population’s preferences for such models. This article analyses the attitudes towards gender roles, and family model preferences within a normative and socio-structural framework. Using data from the International Social Survey Programme 2012, we developed descriptive and explanatory analyses. The findings reveal contradictions between att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 71 publications
0
6
0
1
Order By: Relevance
“…As modern contraception has allowed women greater control over reproduction at the same time that employment opportunities have expanded, those who prefer careers to family-centred activities are increasingly able to exercise their innate tendencies. However, Moreno-Mínguez et al (2018) found that, rather than innate tendencies, gender roles in family life are influenced by significant external socio-structural factors such as age and education. Pfau-Effinger's (2004, 2012 theory of a gender culture also suggests that innate preferences may be less influential on the division of labour in family life than social values concerning employment of family members and parental roles in child care.…”
Section: Theoretica L Perspe Ctivesmentioning
confidence: 99%
“…As modern contraception has allowed women greater control over reproduction at the same time that employment opportunities have expanded, those who prefer careers to family-centred activities are increasingly able to exercise their innate tendencies. However, Moreno-Mínguez et al (2018) found that, rather than innate tendencies, gender roles in family life are influenced by significant external socio-structural factors such as age and education. Pfau-Effinger's (2004, 2012 theory of a gender culture also suggests that innate preferences may be less influential on the division of labour in family life than social values concerning employment of family members and parental roles in child care.…”
Section: Theoretica L Perspe Ctivesmentioning
confidence: 99%
“…That is, the advances in the public sphere reflected in indicators on women's jobs and education are not matched by advances in family work, where inequality is manifest. The interpretive paradigms of work-family reconciliation have found it difficult to incorporate the distinctive characteristics of the Mediterranean family model of reconciliation when interpreting this ambivalence (Moreno-Mínguez et al, 2019 ). We see proof of this difficulty in studies conducted during the pandemic on liberal countries such as the United Kingdom, which stress that they find no evidence of retraditionalization of gender roles (Galasso and Foucault, 2020 ; Hupkau and Petrongolo, 2020 ).…”
Section: The Debate On Work-family Reconciliation In Pre-covid Sociol...mentioning
confidence: 99%
“…All of the foregoing is reflected in cultural ambivalences that make egalitarian advances more difficult in work-family reconciliation practices (González and Jurado Guerrero, 2015 ). The pandemic has strengthened and exposed the attitudinal ambivalence that existed previously in symbolic representations of the family in Spain (Moreno-Mínguez et al, 2019 ; Seiz et al, 2019 ).…”
Section: Conclusion: Future Challenges For Reconciliation Following C...mentioning
confidence: 99%
“…Durante las últimas décadas, la diversidad de modelos de familia ha aumentado en la sociedad española, en paralelo a un aumento significativo del empleo femenino y a la transformación del modelo tradicional del sostén familiar masculino (Moreno-Mínguez, Ortega-Gaspar, & Gamero-Burón, 2019). El desafío de conciliación de vida laboral y familiar que plantea el empleo de los dos miembros de la pareja se ha resuelto mediante distintas estrategias que, fundamentalmente, han descansado en la solidaridad familiar (Tobío et al, 2010;Meil y Rogero-García, 2014), en el recurso a servicios formales de cuidado infantil (en adelante, SFCI) y, aunque en menor medida, en la contratación de cuidadores privados en el hogar y en otras fórmulas de cuidado más minoritarias como las "madres de día" o cuidadoras/es contratadas/os que trabajan fuera del hogar.…”
Section: Introductionunclassified